Microwave Technologies: Recent Advances and New Trends and Applications (IntechOpen, 2024)
This book is intended to serve as a technology reference for graduate students, researchers, and engineers on various microwave engineering subjects. The chapters encompass a wide range of topics in microwave engineering from its core science for developers to state-of-the-art applications for its users. Besides the fundamental technology-related chapters, such as advanced analysis techniques of microstrip structures using the finite difference time domain in Julia and tunable microwave filter designs, there are chapters covering implementations of microwave technology in different applications such as medical imaging, medical heating, food drying, and remote sensing for radio astronomy. The chapters are written based on a collection of theses, research papers, and case analyses by field experts and academicians. The title of the book reflects that each chapter elaborates on a recent advancement or a brand-new application of microwave engineering.